Effect of HIV and Antiretroviral Treatment on Auditory Functions - Minhas, Ravinder S.; Iyengar, Dhanashree A.; Thakur, Jagdeep S.; Azad, Ramesh K. (International Archives of Otorhinolaryngology, 2018)
Introduction Numerous studies have evaluated auditory functions in human immunodeficiency virus (HIV) patients; however, these studies had a few major limitations in terms of methodology as they used mainly evoked audiometry although this method is expensive, time consuming and not widely available. Therefore, we conducted a study in naïve HIV subjects with routine audiometry.Objective To determine the effect of HIV and of the drugs used to treat it on the auditory functions.Methods A prospective observational study was conducted in a medical college with 25 naive HIV-seropositive patients for over a year. Pure tone audiometry (250–8,000 Hz) and CD4 T-lymphocyte count were performed at the time of enrollment and 6 months after commencement of highly active antiretroviral treatment.Results The subjects had increased hearing thresholds at high frequencies (4 KHz and 8KHz) in both ears at the time of enrollment that persisted at the same level (p > 0.05) on follow-up at 6 months. None of the subjects had any other otological symptom during the 6 months of observation. Seven subjects had sensorineural hearing loss in one or both ears at 0 and 6 months. These observations did not show any significant difference on Wilcoxon-signed-rank test. Spearman correlation did not find a significant correlation (p > 0.05) between CD4 T-lymphocyte counts and pure tone audiometry during the study.Conclusion We found high-frequency hearing loss in all subjects with no relation with highly active antiretroviral therapy (HAART) and severity of the disease. This study advocates hearing assessment with pure tone audiometry in HIV subjects so that intervention can be initiated in a timely manner.
Keywords: HIV; hearing loss; audiometry; CD4 T-lymphocyte count